Tea and coffee consumption and risk of laryngeal cancer: a systematic review meta-analysis. - Jiangbo Chen; Shuo Long (PLoS ONE)
Background Tea and coffee are the most commonly consumed beverages in the worldwide. The relationship between tea and coffee consumption on the risk of laryngeal cancer was still unclear. Methods Relevant studies were identified by searching electronic database (Medline and EMBASE) and reviewing the reference lists of relevant articles until Oct. 2013. Observational studies that reported RRs and 95% CIs for the link of tea and coffee consumption on the risk of laryngeal cancer were eligible. A meta-analysis was obtained to combine study-specific RRs with a random-effects model. Results A total of 2,803 cases and 503,234 controls in 10 independent studies were identified. The overall analysis of all 10 studies, including the case-control and cohort studies, found that tea drinking was not associated with laryngeal carcinoma (RR = 1.03; 95% CI: 0.66-1.61). However, coffee consumption was significantly associated with the laryngeal carcinoma (RR = 1.47; 95% CI: 1.03-2.11). A dose-response relationship between coffee intake and laryngeal carcinoma was detected; however, no evidence of dose-response link between tea consumption and laryngeal carcinoma risk was detected. Conclusions The results from this meta-analysis of observational studies demonstrate that coffee consumption would increase the laryngeal cancer risk, while tea intake was not associated with risk of laryngeal carcinoma.